2007
DOI: 10.1007/s11270-007-9395-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ultra Trace Level of Uranium in Ground Water of Different Geo-Chemical Environment by Adsorptive Stripping Voltammetry

Abstract: The mineral mobilisation in ground water due to rock water interaction largely depends on the localized subsurface geo-chemical environment. During this work, traces of uranium were measured by adsorptive stripping voltametry (AdSV) in groundwater having various level of dissolved minerals. Experimental solutions were prepared in the laboratory by spiking natural groundwater with standard solutions of major cations (Ca 2+ , Mg 2+ , K + ), anions (Cl −1 , F −1 , and PO 3À 4 ), trace metal ions (Cu and Pb) and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The electrodes based on mordant Blue 9 32, 3‐ N ‐benzoyl‐ N ‐phenyl hydroxylamine 28, aluminon 33, cupferron 2528, L ‐3‐(3,4‐dihydroxyphenyl)alanine (LDOPA) 29,30, catechol 31, propyl gallate 28, 4‐(2‐hydroxyethyl)‐1‐piprazineethane sulfonic acid 46, and oxine 28 suffer from severe interferences by several metal ions. Although, the interference from several elements, when present at concentrations higher than their tolerance level, can be eliminated by adding complexing agents such as EDTA for Cu(II), Cd(II), Pb(II), and Zn(II), or precipitating with urea for Al(III), Th(IV), Bi(III), Fe(III), and Sn(IV) 24,28,30,31,37. However, comparison of the tolerance levels of the proposed method with other reports on ACSV determination of U(VI), suggests a fair degree of selectivity of the present method (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The electrodes based on mordant Blue 9 32, 3‐ N ‐benzoyl‐ N ‐phenyl hydroxylamine 28, aluminon 33, cupferron 2528, L ‐3‐(3,4‐dihydroxyphenyl)alanine (LDOPA) 29,30, catechol 31, propyl gallate 28, 4‐(2‐hydroxyethyl)‐1‐piprazineethane sulfonic acid 46, and oxine 28 suffer from severe interferences by several metal ions. Although, the interference from several elements, when present at concentrations higher than their tolerance level, can be eliminated by adding complexing agents such as EDTA for Cu(II), Cd(II), Pb(II), and Zn(II), or precipitating with urea for Al(III), Th(IV), Bi(III), Fe(III), and Sn(IV) 24,28,30,31,37. However, comparison of the tolerance levels of the proposed method with other reports on ACSV determination of U(VI), suggests a fair degree of selectivity of the present method (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…), pH, dissolved organic compound (DOC), accumulation potential etc. on determination of ultra trace levels of uranium in groundwater was studied previously by conducting a laboratory experiment [41,42] which revealed that ions do not have any pronounced impact on the analysis of uranium using AdSV. In fact, other metals, varying in wide range in water bodies also form complexes with chloroanilic acid and get adsorbed on mercury electrode.…”
Section: Estimation Of Uranium Concentration Using Adsvmentioning
confidence: 99%
“…Over the past few decades, many studies have focused on the coordination chemistry of uranyl ion, both for extracting and determination of the toxic analyte in different environments. Trace levels of uranium can be determined and quantified, for example, by stripping voltammetry (with modified and nonmodified electrodes), spectrophotometry, fluorimetry, electrochemical impedance spectroscopy (EIS), etc. A previous study conducted in our lab described the electrochemical detection of uranyl by an electrode modified with derivatives of calix[6]­arene, also known as “super uranophile” . The work further investigated the electrochemical determination of UO 2 2+ by a phosphate-based self-assembled monolayer .…”
mentioning
confidence: 99%